Urgensi Kepemimpinan Pendidikan Islam - Shella Masrofah; Muhammad Abul Khair; Alifa Nida; Eva Zulvi; Fandi Ahmad (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2021)
Leadership is an ability that everyone needs to have. The existence of this research on Islamic education leadership aims to reveal the urgency of leadership in Islamic education. This study uses a qualitative descriptive analysis method. The approach used in this research is the library research approach or library method. An education is a person's ability to regulate, move, influence, motivate and direct people who are members of educational institutions so that the implementation of education can run more effectively and efficiently. Leadership in Islamic educational institutions is very important for achieving an educational goal. Because without leadership in educational institutions, the process of implementing education will not run as it should. To achieve this, a leader in an educational institution must have characteristic leadership and is also proficient in self-management that is adapted to his environment. It can be said that a good leader in an educational institution, of course, must master these two things.